Cracking the code for maintaining quality training in Olympic distance triathlon: lessons learnt from a squad of elite Scandinavian athletes - Eleanor Boyle; Corrie Myburgh; Tobias Hansen; Anders Holm Beck (BMJ Open Sport & Exercise Medicine)
Objective High-quality training is a key determinant of performance in the Olympic distance triathlon and is potentially influenced by a unique array of context-specific biopsychosocial factors. Our objective was to explore and describe these factors among squad members of a university-based, elite Olympic distance triathlete developmental programme.Method A qualitative investigation using a visual communication tool-assisted focus group and longitudinal semistructured individual interviews was conducted. Responses were solicited from the University of Southern Denmark’s elite triathlon team (n=8), and inductive coding from the focus group formed the basis of questions for the two rounds of individual interviews 11 months apart. All interviews were transcribed verbatim and then analysed thematically.Results Seventeen context-relevant factors were identified and 10 themes emerged, these being ‘the cold weather ritual’, ‘digestive system conditioning’, ‘the curse of the night owl’, ‘the strings attached to sponsorship’, ‘my coach—my rock’, ‘mood maintenance’, ‘the asynchronous training rhythm’, ‘psychological slavery’, ‘the legacy of the asphalt tattoo’ and ‘the tension of family and friends’.Conclusions By reflecting on their personal training vortex, elite triathletes were able to provide context-relevant insights into the maintenance of training quality over the course of a competitive season. Further research is required to elucidate whether and how biopsycholosocial factors can be modified to optimise the achievement of training goals.